Intelligentsia : ο κύκλος των ποιητών. - Βαρβαρήγος, Δημήτρης, 1951- (Εντύποις, 2015)
Συμμετέχουν οι ποιητές: Δεμπερδεμίδου Γεωργία Δημητρακάκη Χρυσούλα Ιωάννου Νιόβη Κανελλοπούλου Ντινοδήμου Όλγα Κοσεγιάν Χαρα Κυριάκη Αφροδίτη Λύτρα Ελένη Ματζουράνη Τζούτζη Μελισσουργού Βασιλική Μελίτα Πολαρντ Ρούλα Μέμου Βούλα Πολέμη Φάνυ Πουλημενάκου Τζούλια Ραμανδανη Κατερίνα Τσαμπά Μάιρα Φατούρου Λένα Χαδούλη Σύλια